Effects of Fermentation on the Quality, Structure, and Nonnutritive Contents of Lentil (Lens culinaris) Proteins. (13th May 2021) - Alrosan, Mohammad; Tan, Thuan-Chew; Mat Easa, Azhar; Gammoh, Sana; Alu'datt, Muhammad H.
Abstract : Protein digestibility, secondary protein structure components, sugars, and phenolic compounds were analysed to investigate the effect of fermentation on the quality, structure, digestibility, and nonnutritive contents of lentil ( Lens culinaris ) proteins (LPs). Fermentation was carried out using water kefir seed. The initial pH of the unfermented LPs (6.8) decreased to pH 3.4 at the end of the fermentation on day 5. Protein digestibility increased from 76.4 to 84.1% over the 5 days of fermentation. Total phenolic content increased from 443.4 to 792.6 mg of GAE/100 g after 2 days of fermentation, with the sums of the detected phenolic compounds from HPLC analysis reaching almost 500 mg/100 g. The predominant phenolic compounds detected in fermented LPs include chlorogenic and epicatechin, while traces of rutin, ferulic acid, and sinapic acid were observed. Fermentation played a major role in the changes of the components in the secondary protein structure, especially the percentage of α -helices and random coils. In addition, the reduction in α -helix: β -sheet ratio with the increase in protein digestibility was related to the prolongation of the fermentation time. The model used in this research could be a robust tool for improving protein quality, protein degradation, and nonnutritive nutrients using water kefir seed fermentation.